2018
DOI: 10.1002/brb3.1069
|View full text |Cite|
|
Sign up to set email alerts
|

Botulinum toxin A modifies nociceptive withdrawal reflex in subacute stroke patients

Abstract: ObjectivesThe aims of this study were to evaluate the pattern of the nociceptive withdrawal reflex (NWR) of the upper limb at rest and after injection of Botulinum toxin type A (BoNT‐A) in poststroke subacute hemiparetic patients.MethodsFourteen patients with poststroke subacute hemiparesis underwent clinical and instrumental evaluation and BoNT‐A injection. Painful electrical stimulation was applied to induce the NWR. Baseline EMG activity and NWR recordings (EMG and kinematic response) were performed at T0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…There was a lack of significant correlation between the max RsE value and the MAS values for all tested subjects. A decrement of the MAS values after BT injection has been reported earlier by other research groups and attributed to the unavailability of the fibers with active NMJ innervation [30,31]. Despite the fact that primary actions of BT are centered around the NMJ of the injected muscle, the recovery of motor outflow (measured by RsE values during the voluntary contraction) lags the recovery of MAS, which is likely an issue due to the lack of resolution of the MAS.…”
Section: The Difference In Clinical Scores (Mas and Fms) And Rsementioning
confidence: 52%
See 1 more Smart Citation
“…There was a lack of significant correlation between the max RsE value and the MAS values for all tested subjects. A decrement of the MAS values after BT injection has been reported earlier by other research groups and attributed to the unavailability of the fibers with active NMJ innervation [30,31]. Despite the fact that primary actions of BT are centered around the NMJ of the injected muscle, the recovery of motor outflow (measured by RsE values during the voluntary contraction) lags the recovery of MAS, which is likely an issue due to the lack of resolution of the MAS.…”
Section: The Difference In Clinical Scores (Mas and Fms) And Rsementioning
confidence: 52%
“…Reduction of contractile force and of the RsE after the intramuscular injection is assumed to be primarily attributable to the reduced active muscle fiber population, which can be explained by the BT induced presynaptic blockade of the cholinergic transmission [ 6 , 36 ]. Faster recovery of force may be due to altered load sharing activity from synergistic muscles during flexion [ 31 , 37 ], thus our force measurement is potentially impacted by actions of other synergistic flexors. Whereas, the RsE values reflect injected muscle characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have investigated changes in NWR excitability in post-stroke hemiparetic patients with limb motor deficits ( Spaich et al , 2006 ; Serrao et al , 2012 ; Rueterbories et al , 2013 ; Spaich et al , 2014 ). The NWR-related EMG kinematic responses were increased and NWR modulation impaired in stroke patients with hemiparesis ( Serrao et al , 2012 ; Alvisi et al , 2018 ). The NWR-based functional electrical therapy was found to be useful in the rehabilitation of gait in severely impaired hemiparetic patients by improving post-treatment walking velocity and gait symmetry ( Spaich et al , 2014 ; Gervasio et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we demonstrated that, in subjects with upper limb spasticity, the BoNT-A injection reduced in parallel the degree of spasticity and the size of the nociceptive withdrawal reflex (NWR) response of the upper limb, irrespective of the site of injection [20]. The NWR is an objective nociceptive reflex response mediated by a central circuitry sustained by WDR neurons [21], so these data support an intrinsic antinociceptive effect of the BoNT-A, encouraging further studies.…”
Section: Introductionmentioning
confidence: 99%